Enhanced Electromechanical Properties of 0.65Bi1.05FeO3–0.35BaTiO3 Ceramics through Optimizing Sintering Conditions. Issue 12 (19th April 2020) - Ahmed, Tauseef; Khan, Salman Ali; Akram, Fazli; Bae, Jihee; Choi, Soo Yong; Hussain, Ali; Song, Tae Kwon; Sung, Yeon Soo; Kim, Myong-Ho; Lee, Soonil
Abstract : Lead‐free piezoelectric 0.65Bi1.05 FeO3 –0.35BaTiO3 (BF–35BT) ceramics are synthesized via conventional solid‐state reaction by varying sintering dwell time ( t s ). The crystalline phase, microstructures, and piezoelectric properties of BF–35BT are evaluated at room temperature. BF–35BT ceramics with improved electrical properties in a narrow range of t s are obtained. Enhanced electromechanical properties are obtained in ceramics sintered at 1000 °C for 3 h. X‐ray diffraction reveals a single perovskite structure with pseudocubic symmetry. A prominent enhancement in remanent polarization ( P r ) and coercive field ( E c ) is obtained. Typical ferroelectric behaviors are obtained, whereas unipolar and bipolar strains are enhanced with increasing t s . The static piezoelectric constants ( d 33 ) = 187 pC N −1, whereas dynamic piezoelectric constants ( d * 33 ) = 387 pm V −1 at a field of 5 kV mm −1 with Curie temperature ( T C ) = 422 °C. Abstract : Pb‐free 0.65Bi1.05 FeO3 –0.35BaTiO3 (BF–35BT) piezoceramics are synthesized via conventional solid‐state reaction by varying sintering dwell time ( t s ) to study its effect on electromechanical properties. t s has a profound effect on grain size and density of composition, showing that for t s  = 3 h, enhanced electromechanical properties are achieved with a maximum relative density of 96.61% and grain size of 5.41 μm.